GRAMMATICAL ERRORS IN WRITTEN ENGLISH: A CASE STUDY OF MALE AND FEMALE EFL STUDENTS ACROSS DIFFERENT MOTHER TONGUES - Ilyas Ilyas; Asman Bin Mohd Tahir; Nursidah Nursidah (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2025)
This study investigates grammatical errors in English writing produced by male and female EFL students from different mother tongue backgrounds (Makassarese, Bugis, and Javanese). Using a qualitative descriptive case study design, six participants, three males and three females, were asked to compose 150-200 words essay on the topic “The Benefits of Using Cell Phones” to examine how gender and mother tongue influence grammatical accuracy. The errors were identified and categorized using Dulay et al.’s (1982) surface strategy taxonomy, consisting of omission, addition, misformation, and misordering. The analysis revealed that the Bugis male student demonstrated the highest frequency of omission errors, while the Makassarese male student produced the fewest. Both male and female students showed similar patterns in addition errors, with the Bugis and Makassarese female students recording the highest counts. Misformation errors were most frequently found in the Bugis male student and the Makassarese female student, whereas misordering errors were also common among the same two participants. Overall, the findings indicate that mother tongue plays a substantial role in shaping the types and frequencies of grammatical errors committed by male and female EFL learners. These results highlight the importance of recognizing linguistic background in instructional planning, enabling educators to design targeted teaching strategies to improve grammatical accuracy. Moreover, the findings can assist curriculum developers in constructing more inclusive and effective programs that address the specific learning needs of students from diverse mother tongue backgrounds.